ANALISIS FAKTOR-FAKTOR PENYEBAB KEGAGALAN INCUMBENT PEREMPUAN PADA PEMILIHAN LEGISLATIF DPRD KOTA SEMARANG TAHUN 2014 - Putri Kumalasari; Fitriyah . (Journal of Politic and Government Studies, 2018)
In the 2014 legislative election in Semarang City DPRD there were a number of incumbent women who failed to occupy the same position as before. This is estimated because of the same pattern experienced by the incumbent. So the writer with this research tries to answer a question is there the factors underlying the failure of the incumbent failed in the legislative election, where later there will be two internal and external factors to answer the cause of their failure.The research method used is qualitative descriptive. With primary data sources in the form of interviews with research objects, namely the members of the Semarang City DPRD who failed to return to office. And secondary data is used in the form of data from the KPU regarding the legislative elections that took place in the period 2009 - 2014 and the period 2014 - 2019.The results showed that the pattern of failure experienced by the incumbents was almost the same, which was caused by a factor of low individual voice. Three of them were from the same party and claimed that the cause of this was the internal influence of the party. In addition, the fact shows that the C1 form used by the polling committee at the time was different between those owned by special witnesses at the polling station and the results in the villages and sub-districts. So it was alleged that there were fraudulent acts by the polling committee.So recommendations for the government are expected to make strict rules related to fraud which often occur in vote counting activities. As for the party as an agent of political socialization, it is also expected to be a solid party and can work well together with its cadres. So that later it can create a strong synergy to advance the country with clean politics.Keyword: women incumbents, factors that cause failure